PARENTAL MAGMAS OF LUNAR TROCTOLITES: GENETIC PROBLEMS AND ESTIMATED ORIGINAL COMPOSITIONS - Ariskin A.A. (My University, 2007)
The paper presents a review of hypotheses of the early magmatic differentiation of the Moon and petrogenetic processes responsible for the origin of the parental magmas of the magnesian suite of the highland crust. An important role of hybridism of the parental magmas is discussed in the context of the transformations of the melting products and the differentiation of the subchondritic mantle via anorthosite assimilation. These processes are thought to have proceeded simultaneously with the consolidation of the anorthosite crust and resulted in high-Mg magmas, which later gave rise to troctolites, norites, and gabbronorites. An updated version of the METEOMOD model was utilized for simulations of the composition of primitive troctolite melts corresponding to equilibrium with olivine of the composition Fo 88 and Fo 91. The differences between the simulated melt compositions are interpreted with regard for variations in the temperature and composition of the parental magnesian liquids that assimilated compositionally similar feldspathic material. The compositional data obtained are a necessary component of a thermochemical model of assimilation that would also involve the enthalpy of phase transitions and the heat capacity for the reactants and products of crystallization associated with the partial dissolution of anorthosites in high-temperature magmas.